Mortgage interest rates, country risk and maturity matching in Colombia (2008)
In this paper, we examine the determinants of mortgage loans interest rates in Colombia during the period January 2002 - June 2006. We find that the main macroeconomic determinant is public debt interest rates. At the micro level, we find that credit risk is the main determinant. We demonstrate and analyze the tight relationship between country risk and mortgage debt interest rates. This relationship has been growing over time, as banks have increased their share of long-term liabilities in an effort to reduce the maturity mismatch that characterized their balance sheets prior to the 1998-99 financial crisis. Nevertheless, the reduction in the maturity mismatch has left mortgage rates more exposed to country risk variations.